The Complete Works for Solo Piano = L’oeuvre pour piano seul – by Calixa Lavallée, compiled and edited by Brian C. Thompson (score review) - Jurkowski, Edward (CAML Review / Revue de l'ACBM, 2017)
[no abstract]